Penguatan Literasi Digital melalui Model Pengembangan Kurikulum SMA Islam Berbasis Media Digital di Era 4.0 - Bachtiar Adi Saputra; Nurdiansyah Nurdiansyah (Pendidikan Agama Islam STIT Palapa Nusantara, 2020)
This paper aims to describe the strengthening of digital literacy through the development of digital media based Islamic high school curriculum in facing the challenges in 4.0 era. The method used in this study uses a qualitative descriptive approach with data collection techniques through direct observation and interviews. Based on the results of first observations at SMA Muhammadiyah 1 Park, the condition of the school has the potential that has not been maximized, namely the use of digital media in learning. Strengthening digital literacy is done through a model of curriculum development based on digital media in designing objectives, materials, strategies and evaluating learning. The digital literacy component that is the focus of research includes skills in information literacy and media literacy; digital scholarship skills, media literacy, learning skills, ICT literacy through guided assignments using digital media; and communication and collaboration skills through the active participation of students by using their digital media to collaborate and communicate in learning. This research is expected to make a positive contribution in the model of curriculum development in Islamic high schools that is in line with the times, through strengthening digital literacy to face challenges in 4.0 era.